2022
DOI: 10.1080/08897077.2022.2060439
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Peer and Parental Attitudes toward Substance use and Actual Adolescent Substance Use: The Impact of Adolescent-Confidant Relationships

Abstract: Objective: While peer influence is a well-documented risk factor for adolescent substance use, it remains unclear whether peer or parental attitudes have greater impact, and if this relationship is moderated by having a confidant and the relationship between adolescents and their confidant. Method: Pooled (2015-2018) National Survey on Drug Use and Health (NSDUH) data on adolescents (12-17 years) were used. Perceived peer and parental disapproval of tobacco, alcohol, and marijuana use were dichotomized. We ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 45 publications
0
3
0
1
Order By: Relevance
“…Thus, social conformity and sensation seeking ("for fun") motives that are common in the literature are often mentioned by youth, although youth mentioned "being cool/ tough" and enjoyment (sensory) motives more often whereas these motives are not typically considered in adolescent risktaking research. Hence, it would be for example interesting for research to investigate whether the motives coolness and enjoyment predict adolescent substance use to a similar extent as more often investigated factors such as peer influence and sensation seeking, As mentioned above, the research literature over the years has focused on social influences, with strong evidence that both family (Donovan, 2004) and peer use (Leung et al, 2011) are associated with greater likelihood of trying alcohol as well as tobacco and cannabis (Marziali et al, 2022). There is also strong evidence that advertising for alcohol on television and in magazines encourages adolescent trial (Smith and Foxcroft, 2009).…”
Section: Current Descriptions Of Adolescents' Motivations For Engagin...mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, social conformity and sensation seeking ("for fun") motives that are common in the literature are often mentioned by youth, although youth mentioned "being cool/ tough" and enjoyment (sensory) motives more often whereas these motives are not typically considered in adolescent risktaking research. Hence, it would be for example interesting for research to investigate whether the motives coolness and enjoyment predict adolescent substance use to a similar extent as more often investigated factors such as peer influence and sensation seeking, As mentioned above, the research literature over the years has focused on social influences, with strong evidence that both family (Donovan, 2004) and peer use (Leung et al, 2011) are associated with greater likelihood of trying alcohol as well as tobacco and cannabis (Marziali et al, 2022). There is also strong evidence that advertising for alcohol on television and in magazines encourages adolescent trial (Smith and Foxcroft, 2009).…”
Section: Current Descriptions Of Adolescents' Motivations For Engagin...mentioning
confidence: 99%
“…As mentioned above, the research literature over the years has focused on social influences, with strong evidence that both family ( Donovan, 2004 ) and peer use ( Leung et al, 2011 ) are associated with greater likelihood of trying alcohol as well as tobacco and cannabis ( Marziali et al, 2022 ). There is also strong evidence that advertising for alcohol on television and in magazines encourages adolescent trial ( Smith and Foxcroft, 2009 ).…”
Section: Adolescents’ Motivations For Engaging In Risk Behaviormentioning
confidence: 99%
“…A number of studies among adolescents attending mainstream schools have confirmed that being around peers who use psychoactive substances fosters substance use [50]. The perception of peer behaviour is even more important; if young people are convinced that their peers use psychoactive substances and accept behaviour of that kind (which is not necessarily true), they are more likely to use them themselves [51][52][53]. The perceived behaviour of non-familial adults who adolescents meet in their immediate environment is also important.…”
Section: ■ Omówieniementioning
confidence: 99%
“…W wielu badaniach wśród nastolatków uczęszczających do szkół ogólnodostępnych potwierdzono, że obracanie się w kręgu rówieśników, którzy używają substancji psychoaktywnych, sprzyja sięganiu po te substancje [50]. Bardziej istotne jest przy tym postrzeganie zachowań rówieśników -jeśli młodzi ludzie są przekonani, że ich koledzy i koleżanki używają substancji psychoaktywnych oraz akceptują takie zachowania (co nie musi być zgodne z prawdą), wtedy sami są bardziej skłonni po nie sięgać [51][52][53]. Istotne znaczenie ma także postrzeganie zachowań osób dorosłych spoza rodziny, których nastolatkowie spotykają w swoim najbliższym otoczeniu.…”
Section: ■ Omówienieunclassified